2002
DOI: 10.1111/1475-3588.00014
|View full text |Cite
|
Sign up to set email alerts
|

ADHD: A Survey of Psychiatric and Paediatric Practice

Abstract: Most child and adolescent psychiatrists and community paediatricians have a heavy commitment to the assessment and management of children with ADHD. The paediatric approach is heavily biased toward clinical investigation and psychostimulant treatment. Child and adolescent psychiatrists prioritise mental health assessment and have access to a wider range of treatment options. This survey clearly suggests the need for joint working between the two disciplines to provide a holistic approach to the condition to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 17 publications
2
19
0
1
Order By: Relevance
“…Our study has shown (Figure 3) that CAMHS services frequently offer a number of different therapies for treatment of ADHD, especially occupational therapy (95%) and speech and language therapy (97%), while these therapies are not so readily available in paediatric clinics. The same result was also found in the UK survey, carried out by Salmon & Kemp (2002). Multidisciplinary teams are known to have an important role in treating multi-systemic issues related to ADHD (academic, social, family impact), aiming to improve long-term outcome, as urged by some ADHD reviews (Turgay, 2007;Storebø et al, 2015) and Clinical Guidelines (CADDRA, 2011).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Our study has shown (Figure 3) that CAMHS services frequently offer a number of different therapies for treatment of ADHD, especially occupational therapy (95%) and speech and language therapy (97%), while these therapies are not so readily available in paediatric clinics. The same result was also found in the UK survey, carried out by Salmon & Kemp (2002). Multidisciplinary teams are known to have an important role in treating multi-systemic issues related to ADHD (academic, social, family impact), aiming to improve long-term outcome, as urged by some ADHD reviews (Turgay, 2007;Storebø et al, 2015) and Clinical Guidelines (CADDRA, 2011).…”
Section: Discussionsupporting
confidence: 58%
“…A survey of ADHD practice among consultant child and adolescent psychiatrists, compared with consultant hospital and community paediatricians in UK (Salmon & Kemp, 2002), showed that both groups recommend medication when necessary; however child psychiatrists have more access to multidisciplinary mental health services than paediatricians, and thus can offer more parental support. Still regarding possible differences between child psychiatrists and paediatricians towards ADHD, Venter et al (2004) found both groups considered contact with school staff an important aspect of treatment, although paediatricians placed more emphasis on this than psychiatrists.…”
Section: Introductionmentioning
confidence: 99%
“…But he wants it to be consistent, normal time. Not over Easter Only 30% of doctors agree or strongly agree that drug holidays from ADHD medication should be incorporated Salmon and Kemp (2002) Survey -Almost 60% of the surveyed participants were reported to consider trial without the medication on an annual basis Hazell, McDowell, and Walton (1996) Survey Stimulants Almost 70% of children who had been receiving medication for a year will stop it at some time, but only in 34% stopping the medication was planned in order to determine whether the medication is still needed…”
Section: Is the Medication Still Needed?mentioning
confidence: 99%
“…A oscilação nos achados quanto à prevalência indica que os resultados variam de acordo com os critérios utilizados para se avaliar o transtorno e de acordo com a população que é avaliada (Aggarawal & lillystone, 2000). As pesquisas seguem os mais diversos métodos e utilizam inúmeros instrumentos, logo, a confirmação do diagnóstico está muito relacionada com a metodologia utilizada e com a rigorosidade do pesquisador, fato que se repete na práti-ca diária de profissionais da saúde (Salmon & Kemp, 2002). Essa perspectiva aponta para a necessidade de uma avaliação criteriosa que utilize diversos instrumentos e se beneficie de uma troca interdisciplinar entre os profissionais da saúde (psicólogos, psiquiatras, psicopedagogos, neurologistas).…”
unclassified